Sternocleidomastoid Tendon as a Consistent Landmark for Identifying the Spinal Accessory Nerve: A Case Series. Issue 2 (June 2022) - McCann, Adam; Boeckermann, Lauren; Jawad, Basit A.; Moreno, Kattia; Patil, Yash
Objective: We propose a standardized approach of using the tendon of the sternocleidomastoid (SCM) muscle to locate the spinal accessory nerve (SAN) in neck dissection. Study Design: Cross-sectional anatomic study. Setting: Tertiary academic medical center. Methods: Adult patients aged ≥18 years undergoing primary neck dissection for head and neck cancer were included. Anatomic measurements included the length of the SCM tendon, the distance from the mastoid tip to the entrance of the SAN into the SCM, the distance from the SAN to the distal edge of the SCM tendon, and the perpendicular distance from the anterior edge of the SCM to the SAN. Five cadaveric specimens also underwent bilateral modified radical neck dissections with the same anatomic measurements taken. Results: Twenty-two living subjects and 5 cadavers were included. No statistical correlation was noted between patient demographics and any measurement. The mean (SD) length of the SCM tendon was 63.7 mm (11.8) in living subjects and 61.5 mm (10.4) in cadaveric specimens. The average distance from the mastoid tip to the entrance of SAN into the SCM was 51.6 mm (12.2) in living subjects and 51.6 mm (7.1) in cadaveric subjects. The distance of the SAN insertion into the SCM muscle from the anterior edge was 8.9 mm (3.4) in living subjects and 16.2 mm (7.2) in cadaver specimens. Laterality was compared in the cadaveric specimens; there was no statistically significant difference in any of the measurements between sides. Conclusion: This study demonstrates the SCM tendon to be a reliable and safe surgical landmark to identify and preserve the SAN during neck dissection.